Real-world incidence of symptomatic skeletal events and bone-modifying agent use in castration-resistant prostate cancer – an Australian multi-centre observational study. (November 2021) - Anton, Angelyn; Wong, Shirley; Shapiro, Julia; Weickhardt, Andrew; Azad, Arun; Kwan, Edmond M.; Spain, Lavinia; Gunjur, Ashray; Torres, Javier; Parente, Phillip; Parnis, Francis; Goh, Jeffrey; et al.
Abstract: Introduction: Bone metastases occur frequently in castration-resistant prostate cancer (CRPC) and may lead to skeletal-related events (SREs), including symptomatic skeletal events (SSEs). Bone-modifying agents (BMAs) delay SREs and SSEs. However, the real-world use of BMAs is debated given the absence of demonstrated survival advantage and potential adverse events (AEs). Our retrospective study examined BMA use and SSE rates in Australian patients with CRPC. Methods: Patients with CRPC and bone metastases were identified from the electronic CRPC Australian Database. Patient characteristics, treatment patterns and AEs were analysed. Descriptive statistics reported baseline characteristics, SSE rates and BMA use. Comparisons between groups used t-tests and Chi-square analyses. Overall survival was calculated by the Kaplan-Meier method. Results: A total of 532 eligible patients were identified with a median age of 73 years (range: 44–97 years). BMAs were prescribed in 232 men (46%), 183 of whom received denosumab. Patients receiving first-line docetaxel for CRPC were more likely to commence BMAs than those receiving abiraterone or enzalutamide (51% vs 31% vs 38%; p = 0.004). SSEs occurred in 148 men (28%), most commonly symptomatic lesions requiring intervention (75%). At the time of initial SSEs, only 28% were receiving BMAs. Patients treated at sites with lower BMA use (<median) had higher SSE rates (32% vs 22%, p = 0.019). Conclusion: In our real-world cohort, SSEs occurred in almost one-third of patients with CRPC and bone metastases, whereas less than half of patients received BMAs. The lower rate of SSEs in treatment sites with increased BMA use supports their benefit in this setting. Highlights: Symptomatic skeletal events (SSEs), an important complication of bone metastases, occurred in 28% of our cohort. Many SSEs occurred early (48%), before additional systemic therapy for castration-resistant prostate cancer (CRPC). Bone-modifying agents (BMAs) delay the development of SSEs in patients with CRPC and bone metastases. In our multi-centre registry, BMA use was only 46%, with variability in schedules. A greater proportion of patients at sites with lower BMA use developed SSEs (32% vs 22%, p = 0.019).